Indonesia : Report on the Observance of Standards and Codes on Accounting and Auditing - World Bank (World Bank, Washington, DC, 2020)
Reports on the Observance of Standards and Codes Accounting and Auditing (‘ROSC A&A’) assessfinancial reporting and auditing standards, institutions and practices in participating countries.These reports form part of a joint initiative implemented by the World Bank and the InternationalMonetary Fund to review the quality of implementation of internationally recognized standardsand principles in 12 key areas (‘the ROSC program’) with a view to promoting financial andeconomic stability. This report provides an assessment of financial reporting and auditing requirements and practices within the corporate sector in Indonesia and sets forth areas for consideration for improving the institutional environment for A&A. The ROSC A&A used international benchmarks of good practice governing financial reporting and auditing in the assessment, includingInternational Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA).This report updates an earlier assessment which was published in 2011 and was undertakenfollowing a formal request from the Government of Indonesia.